Hubungan riwayat merokok dengan kejadian penyakit paru obstruksi kronik (PPOK) - Syavira Maeva Patricia; Widiastuti Widiastuti; Sigit Harun (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation that is not fully reversible. The condition is mainly caused by chronic inflammation due to long-term exposure to harmful particles or gases, particularly cigarette smoke. Purpose: This study aimed to analyze the relationship between smoking history and the incidence of COPD among patients. Method: This study used an analytic observational design with a cross-sectional approach. A total of 69 respondents were selected using purposive sampling. Data were collected through a smoking history questionnaire and medical record observation sheets. Statistical analysis was performed using the Chi-Square test and Fisher’s Exact Test with a significance level of 0.05. Results: Most respondents were former smokers, and the majority did not experience COPD. Statistical analysis showed no significant relationship between smoking history and COPD incidence (p > 0.05). Conclusion: There was no statistically significant relationship between smoking history and COPD incidence in this study. However, smoking remains an important theoretical risk factor for the development of COPD.   Keywords: Chi-Square; COPD; COPD Occurrence; Fisher’s Exact Test; Smoking History; Patients.   Pendahuluan: Penyakit Paru Obstruktif Kronik (PPOK) merupakan penyakit paru kronis progresif yang ditandai dengan hambatan aliran udara persisten dan menjadi salah satu penyebab kematian tertinggi di dunia. Merokok merupakan faktor risiko utama PPOK, dan tingginya prevalensi perokok di Indonesia berkontribusi terhadap meningkatnya beban penyakit ini. Tujuan: Untuk menganalisis hubungan antara riwayat merokok dengan kejadian PPOK pada pasien. Metode: Observasional analitik dengan pendekatan cross-sectional pada 69 responden yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan melalui kuesioner riwayat merokok dan observasi rekam medis Penelitian. Analisis menggunakan uji Chi-Square dan Fisher’s Exact Test dengan tingkat signifikansi 0.05. Hasil: Sebagian besar responden merupakan eks perokok dan mayoritas tidak mengalami PPOK. Hasil uji statistik menunjukkan tidak terdapat hubungan yang bermakna antara riwayat merokok dan kejadian PPOK (p > 0,05). Simpulan: Tidak ditemukan hubungan signifikan antara riwayat merokok dan kejadian PPOK dalam penelitian ini, meskipun secara teoritis merokok tetap menjadi faktor risiko utama PPOK.   Kata Kunci: Chi-Square; Fisher’s Exact Test; Kejadian PPOK; Pasien;  PPOK; Riwayat Merokok.